Pemanfaatan limbah budidaya ikan lele dumbo sebagai sumber bahan organik untuk produksi bloodworm (Larva Chironomidae). - Bambang Sulistiyarto (Fakultas Peternakan Universitas Kristen Palangka Raya, 2016)
This study aims to examine the use of African catfish farming waste as a source of organic material for producing bloodworm (Chironomidae larvae). Completely randomized design with 3 treatments and 3 replications are used to determine the effect of using African catfish farming waste as a source of organic material with different doses on the biomass of bloodworm. The doses waste used were 0.5 g / L of water, 1.0 g / L of water, and 1.5 g / L of water. The results showed that the dose of the waste highly significant effect on bloodworm biomass harvested. At a dose of 1.5 grams of waste / L obtained the highest yields of bloodworm 14.2 ± 0.4 grams. Bloodworm production positively correlated with pH (r = 0.735) and TDS (r = 0.988). Key words : Bloodworm, Chironomidae larvae, fish culture waste, organic sources.